Inelastic compressive buckling behavior of a cylindrical shell at elevated temperature: Case study. (July 2019) - Seo, Jihye; Won, Deokhee; Kim, Seungjun; Kang, Young Jong
Abstract: A cylindrical shell is a structural form that is widely used in various industries such as for ocean structures, bridges, piers, and buildings. The purpose of this study includes investigating inelastic buckling behavior of a cylindrical shell under uniaxial compression at an elevated temperature and considering geometrically and materially non-linear analysis with imperfections. Selected parameters of the analytical model include fire exposure condition, slenderness ratio, and D/t (diameter/thickness ratio); compressive buckling behavior characteristics of a cylindrical shell were obtained using ABAQUS (a commercial FE Program). The critical buckling strength and mode shape of the cylindrical shell were analyzed through 3D modeling to present basic data for reasonably efficient design. Results indicate that it is necessary to consider nonlinear material and geometric behavior when compared to the case of the slender column. Highlights: The purpose of this study is inelastic buckling behavior of a cylindrical shell under uniaxial compression at an elevated temperature through geometrically and materially non-linear analysis with imperfections. Selected parameters for the analytical model are, slenderness ratio, D/t (diameter/thickness ratio), and fire exposure condition.. Results indicate that it is necessary to consider material and geometric nonlinear behavior when compared to those in the case of the slenderer column.